Relationship between land degradation, biophysical and social factors in Lekso Watershed, East Java, Indonesia - Iva Dewi Lestariningsih; W Widianto; Christanti Agustina; S Sudarto; Syahrul Kurniawan (Journal of Degraded and Mining Lands Management, 2018)
Degraded lands are getting extensive worldwide. Even its existence has projected as a solution to fulfill agricultural land scarcity to meet the global demands of food and other agricultural goods, the rate of its extension should be inhibited. Some factors play important role.  This research was aimed to find the explanation about how degraded land, biophysical and social factors are related. Research site was located in Lekso Watershed, East Java, Indonesia. Land degradation is assessed by evaluation of the critical land status based on procedure established by Indonesia’s Ministry of Forestry in form of Regulation No. P.32/Menhut-II, 2009.A series of field survey using secondary data obtained from GIS tool performed to collect data for quantify the critical land status. Social factors in this study were limited on people perception, awareness and participation. These data collected by in-depth interview to the respondents. Site of presented respondent selected with purposive sampling, while the respondents in each site selected with stratified random sampling method. The research revealed that surface cover demonstrated high correlation and regression toward critical and very critical land (average r = -0.9822, R2= 0.9648). However, slope steepness located in high altitude showed a contrary trend in which increasing slope steepness decreased the number of total moderate, critical and very critical lands. The functional area of this location as protected forest gave a good surface cover on the steep slope and resulted on small area of degraded land. On the other side, negative perception about cultivation on forest and steep slope resulted in positive correlations with the area of very critical land (r = 0.6710 for cultivated forest, and r = 0.9113 for cultivated steep slope). Moreover, people awareness about flood, landslide and drought gave a negative correlation (r = -0.6274) with critical and very critical area. At last, people participation on farmers’ organization could not be used to elucidate the range of degraded land as the participation in this context did not include the competency building about soil and water conservation values.